2013
DOI: 10.1109/twc.2013.062713.130302
|View full text |Cite
|
Sign up to set email alerts
|

Energy and Content Aware Multi-Homing Video Transmission in Heterogeneous Networks

Abstract: Abstract-This paper studies video transmission using a multihoming service in a heterogeneous wireless access medium. We propose an energy and content aware video transmission framework that incorporates the energy limitation of mobile terminals (MTs) and the quality-of-service (QoS) requirements of video streaming applications, and employs the available opportunities in a heterogeneous wireless access medium. In the proposed framework, the MT determines the transmission power for the utilized radio interfaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 36 publications
(77 reference statements)
0
26
0
Order By: Relevance
“…In each of the conducted simulations, we vary the total power consumption at MTs, P T m = [0. 5,3], displayed across the x-axis. The total available power is used in both data transmission and circuit power consumption.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In each of the conducted simulations, we vary the total power consumption at MTs, P T m = [0. 5,3], displayed across the x-axis. The total available power is used in both data transmission and circuit power consumption.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…1 Let M ns ⊆ M denote the subset of MTs which lie in the coverage area of network n BS/AP s. Using the multiple radio interfaces and through the multi-homing capability, each MT can communicate with multiple BSs/APs simultaneously. The bandwidth allocated on the uplink from network n BS/AP s to 1 The video packets streamed among the multiple radio interfaces in transmission can be achieved using a packet scheduling algorithm as in [5].…”
Section: System Modelmentioning
confidence: 99%
“…As one of the 'killer'-applications in contemporary wireless communications systems [154]- [156], video streaming has become a popular research topic, including efficient compression standards [157]- [159], error-concealment/error-resilient streaming techniques [155], [160], [161], as well as reliable transmission schemes [162]- [164], etc.…”
Section: B Video Streamingmentioning
confidence: 99%
“…For example, they increase the transmit power when the average queue lengths increase so as to stabilize the network queue. Also, Ismail et al [26], [27] suggested transmit power control algorithms of mobile devices in heterogeneous networks for energy minimization with target QoS (quality of service) of video when the mobile devices are able to simultaneously transmit the video file through multiple wireless networks (e.g., cellular and WiFi), called multi-homing.…”
Section: Dvfsmentioning
confidence: 99%
“…Proof of Lemma 1 Proof: From the queueing models of networking application (NA), (24) where since the actual service quantity of network part is bounded by actual queue length at time slot . By taking square on the (24) and using the fact that , we have (25) Then, by arranging (25), we have (26) Similarly, we obtain the following by repeating for non-networking application (NNA):…”
Section: Appendix Amentioning
confidence: 99%